Pengaruh Mentoring Gembala Sidang Kepada Pemuda Terhadap Efektivitas Pelayanan Gereja - Yusuf Slamet Handoko; Adventrianis Daeli (Institut Agama Kristen Negeri Manado, 2022)
Youth as leadership successors in the future need to be mentored properly by the pastors. Successful mentoring will produce future leaders who are trained and ready to serve in various church ministries in the future. The purpose of this research is to provide an understanding for pastors on how to mentor youth, teach and motivate youth to serve, thus encouraging pastors to be more effective in carrying out their pastoral duties, bringing youth to understand God's calling for all believers. This research used a correlational method. Based on the data analysis conducted, it is concluded that the mentoring carried out by the pastor has a strong relationship with the involvement of youth in the ministry, because with mentoring that is done well by the pastor, it will have an impact on the progress of the ministry and the increase in youth who are involved in the ministry.